Estrategias didácticas en el rendimiento académico de los estudiantes de octavo año de educación básica de la Unidad Educativa Eugenio Espejo del Cantón Babahoyo Provincia de los Ríos. - Espinoza Gonzabay, Rosa Raquel (2016)
The present final report of research had as an aim to determine the level of influence of the didactic strategies in the academic performance in the eighth year students of the educational unit "Eugenio mirror". During the investigation, surveys were applied to teachers and students. The tabulation of teachers determined that a high percentage considered the implementation of didactic strategies to allow students to improve their school performance. The students indicated that not all teachers use didactic strategies that help to facilitate the learning, reason why in the majority they thought that the teachers should provide a good atmosphere of confidence in the classroom that helps them to obtain gains in their learning without having Than falling into the boring and traditionalist classes, students need an atmosphere of peace and warmth, with the teacher and his classmates. Therefore, the proposal to implement didactic strategies based on workshops with guidelines related to the treatment of the transversal priorities of the curriculum, the fundamental skills and the contents that the teacher through the didactic strategies should be formulating development axes and blocks of Experiences, based on a teacher development profile and general objectives, so that students acquire knowledge, experiences, skills, skills and attitudes that help them achieve meaningful learning in all areas of study.